2019
DOI: 10.1029/2019jc015105
|View full text |Cite
|
Sign up to set email alerts
|

On the Wind Contribution to the Variability of Ocean Currents Over Wide Continental Shelves: A Case Study on the Northern Argentine Continental Shelf

Abstract: The southwestern Atlantic Ocean has one of the largest and most productive continental shelves of the southern hemisphere. Despite its relevance, its circulation patterns have been largely inferred from hydrographic observations and numerical models. Here we describe the variability of the shelf circulation based on the analysis of 11 months of multilevel currents measured by two bottom‐mounted acoustic Doppler current profilers deployed over the continental shelf at 39°S. The record‐length mean is 12 and 13 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 35 publications
(60 reference statements)
3
33
0
Order By: Relevance
“…This negative SLA is confirmed by a coastal tide gauge record from San Clemente del Tuyu (supporting information Figure S3). The change in current direction is in agreement with recent current meter observations collected over the central portion of the continental shelf at around 39°S, which show that though the mean flow is about 10-12 cm s −1 toward the northeast, current reversal are likely to occur during periods of northeasterly winds associated with the passage of synoptic weather systems (Lago et al, 2019).…”
Section: Journal Of Geophysical Research: Oceanssupporting
confidence: 90%
See 2 more Smart Citations
“…This negative SLA is confirmed by a coastal tide gauge record from San Clemente del Tuyu (supporting information Figure S3). The change in current direction is in agreement with recent current meter observations collected over the central portion of the continental shelf at around 39°S, which show that though the mean flow is about 10-12 cm s −1 toward the northeast, current reversal are likely to occur during periods of northeasterly winds associated with the passage of synoptic weather systems (Lago et al, 2019).…”
Section: Journal Of Geophysical Research: Oceanssupporting
confidence: 90%
“…A schematic circulation summarizing these findings is presented in Figure 10. Over and south of the southernmost section, a northeastward flow (blue solid line) represents the mean path of SASW derived from previous work (Lago et al, 2019) but not observed in the October 2013, when SASW flowed southward (blue dashed line) due to the prevailing northeasterly winds blowing at that time. The circulation schematic is similar to those presented by Möller et al (2008) and Piola et al (2008) with the addition of the splitting SASW path near 37°S.…”
Section: Journal Of Geophysical Research: Oceansmentioning
confidence: 78%
See 1 more Smart Citation
“…10.1029/2020JC016813 7 of 16 the along-shore currents is strongly modulated by the cross-shore pressure gradient generated by the alongshore component of the wind stress (Lago et al, 2019). The strong shelf transport response to along-shore winds is readily apparent over the inner and mid-shelf ( Figure 4).…”
Section: In Situ Volume Transport: Large Variability Induced By Localmentioning
confidence: 99%
“…The location of the CASSIS moorings used in this study are displayed in Figure 1. Given the barotropic nature and the cross-shelf coherency of the along-shore flow reported by Lago et al (2019), the available data may be used to provide a robust estimate of the volume transport over the continental shelf. The following sections of the study present the data sets considered and the methods used for the analysis (Section 2), the results and discussions (Section 3) and main conclusions (Section 4).…”
mentioning
confidence: 99%